(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the procedural status of a specialist of a teacher, a psychologist participating in investigative and other procedural actions involving a minor. The functions of a teacher and a psychologist are very close to each other, it is precisely this reason that is considered by some researchers and it is proposed to separate legislatively the teacher, the psychologist as an independent category of procedural persons that are different from the specialist in the criminal process. The study of the current criminal procedural legislation and the practice of its application allows us to justify the author’s definition of the correct definition of the purpose and objectives of the participation of a teacher and a psychologist in the interrogation of a minor. Key words: evidence, proving, justice, juvenile justice, specialist, special knowledge, criminal procedure.